Design of power oscillation damping controller for TCSC device - Nuraddeen Magaji, author; Mohd. Wazir Mustafa, author; International Conference on Control Instrumentation and Mechatronic Engineering (CIM09) (2nd: 2009: Melaka) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL